2023
DOI: 10.1007/s00531-023-02368-5
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic to early Cretaceous geodynamic evolution of the eastern Hellenides

Evripidis Mposkos,
Alexander Krohe,
Craig Walton
et al.

Abstract: Remarkably well-preserved crustal sections from the Eastern Hellenides offer the chance to evaluate the regional geodynamic evolution of continental crust. Here, we identify and geodynamically interpret eclogite facies metamorphism in the Triassic–Jurassic volcano-sedimentary series of the West Circum Rhodope zone in the eastern Hellenides. Equilibrium phase diagrams and measured mineral compositions were used to inform reconstructions of geodynamic evolution during the early Alpine period. We newly define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Model results suggest the existence of a HP/ MT metamorphic event (1.9 GPa/520 °C) preceding a regional re-equilibration at medium-pressure/ medium-temperature conditions (1.2 GPa/620 °C). Mposkos et al (2023) confirmed the tectonic imbrications of garnet mica schists, marbles, quartzites and amphibolites (including eclogitic bodies) of the Western Circum-Rhodope Belt with the Vertiskos migmatitic gneisses. From a garnetkyanite-staurolite mica schist and an eclogitic body from this imbricates, they reported P-T conditions at ~1.7±1 GPa and temperatures of 580-600 °C, and 1.91±0.08 GPa and 640±25 °C, respectively.…”
Section: Vertiskossupporting
confidence: 61%
See 1 more Smart Citation
“…Model results suggest the existence of a HP/ MT metamorphic event (1.9 GPa/520 °C) preceding a regional re-equilibration at medium-pressure/ medium-temperature conditions (1.2 GPa/620 °C). Mposkos et al (2023) confirmed the tectonic imbrications of garnet mica schists, marbles, quartzites and amphibolites (including eclogitic bodies) of the Western Circum-Rhodope Belt with the Vertiskos migmatitic gneisses. From a garnetkyanite-staurolite mica schist and an eclogitic body from this imbricates, they reported P-T conditions at ~1.7±1 GPa and temperatures of 580-600 °C, and 1.91±0.08 GPa and 640±25 °C, respectively.…”
Section: Vertiskossupporting
confidence: 61%
“…For the garnetbearing phyllite from the Melissochori Formation, Kydonakis et al (2015) calculated P-T conditions at 550 °C for P<0.8 GPa during the retrogression following the HP event. Recently, Mposkos et al (2023) reported temperatures of 300-400 °C and minimum pressures of 0.8-0.9 GPa for metapelites from this formation. Burg (2012) suggested that these blueschist facies rocks may have been exhumed in an accretionary wedge during the Late Jurassic-Early Cretaceous evolution of the Rhodope metamorphic complex.…”
Section: Western Circum-rhodope Beltmentioning
confidence: 84%